Simply cut out – Combining CRISPR/Cas9 RNPs and transiently selected telomere vectors for marker free-gene deletion in Trichoderma atroviride - Mario Gründlinger; Chiara Ellensohn; Leo Drechsel; Ulrike Schreiner; Siebe Pierson; Clara Baldin; Susanne Zeilinger (Frontiers in Genome Editing)
Trichoderma atroviride is a well-known mycoparasitic fungus widely used for the biological control of fungal plant pathogens. However, genetic manipulation in this organism remains challenging due to the limited availability of versatile and efficient molecular tools. Here, we present a CRISPR/Cas9-based method for targeted gene manipulation using ribonucleoprotein (RNP) complexes combined with a transiently stable telomere vector. We successfully inactivated three genes—pks4 (spore pigment production), pyr4 (pyrimidine biosynthesis), and pex5 (peroxisomal matrix protein import receptor)—to demonstrate the system’s utility. Although double-strand breaks induced by Cas9 can be repaired via homology-directed repair (HDR), using donor templates, the most effective gene inactivations in our case were achieved via non-homologous end joining (NHEJ), by co-transforming the transiently stable telomere vector carrying the hygromycin-resistance gene (hph), which was rapidly lost under non-selective conditions. This strategy enables marker-free genetic manipulation, supports vector recycling, and simplifies successive transformations. Overall, our method expands the genetic toolbox for T. atroviride, offering a fast and reliable approach for reverse genetics in this agriculturally important fungus.